27.4k views
1 vote
What's the standard form, vertex, and factored​

What's the standard form, vertex, and factored​-example-1
User Lulumeya
by
4.7k points

1 Answer

4 votes

Answer:

1)
f(x)=(x+1)(x-3)

2)
f(x)=(x-1)^2-4

3)
f(x)=x^2-2x-3

Explanation:

So we have a graph and we know that its roots are at x=-1 and x=3.

We also know the vertex is at (1,-4). With that, we can figure out the three forms.

Factored Form:

The factored form, as given, is:


f(x)=a(x-r_1)(x-r_2)

We already know the roots of -1 and 3. So, substitute:


f(x)=a(x-(-1))(x-3)

Simplify:


f(x)=a(x+1)(x-3)

Now, we just need to figure out a. To do so, we can use the vertex. Since the vertex is at (1,-4), this means that f(1) is -4. So, substitute 1 for x and substitute -4 for f(x):


-4=a(1+1)(1-3)

Add and subtract:


-4=a(2)(-2)

Multiply:


-4=-4a

Divide both sides by -4:


a=1

So, our factored form is:


f(x)=(x+1)(x-3)

Vertex Form:

The vertex form is:


f(x)=a(x-h)^2+k

Where (h,k) is the vertex.

We already know the vertex is (1,-4), so substitute 1 for h and -4 for k.

We also previously determined that a is 1, so substitute that also. So:


f(x)=(1)(x-(1))^2+(-4)

Simplify:


f(x)=(x-1)^2-4

Standard Form:

To acquire the standard form, simply expand the factored or vertex form. I'm going to expand the factored form:


f(x)=(x+1)(x-3)

FOIL:


f(x)=x^2-3x+x-3

Combine like terms:


f(x)=x^2-2x-3

And we're done!

User Ichor De Dionysos
by
5.1k points